2021
DOI: 10.24940/ijird/2021/v10/i4/apr21054
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Covid-19 Vaccine Hesitancy among Residents of Plateau State, Nigeria

Abstract: Background: The refusal or delay in acceptance of proven effective vaccines including the newly introduced COVID-19 vaccines, has the potential to adversely affect the control of vaccine preventable diseases. This study was conducted to determine the level and predictors of hesitancy against COVID-19 vaccine that is yet to be made available to the general public in Plateau State among selected residents. Methodology: A scenario-based, cross-sectional study was conducted among 300 selected adults before the ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This was also evident in their responses; possible side effect of the vaccine (80.28%) and rumored controversies (16.30%) surrounding the virus and the proposed vaccine. Okoh et al [10], reported a prevalence of 46% of the respondents in Plateau state with fear of side effect accounting for the highest reason for the hesitancy (17.2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also evident in their responses; possible side effect of the vaccine (80.28%) and rumored controversies (16.30%) surrounding the virus and the proposed vaccine. Okoh et al [10], reported a prevalence of 46% of the respondents in Plateau state with fear of side effect accounting for the highest reason for the hesitancy (17.2%).…”
Section: Discussionmentioning
confidence: 99%
“…The result is also comparable with the findings of Obi Ezeani et al (2) that reported 55% of the study population in Awka metropolis indicated possible side effect as the reason for not willing to take the vaccine. There is need to embark on health education to members of the general public on the importance of COVID 19 vaccination [10]. This will result in more people getting vaccinated.…”
Section: Discussionmentioning
confidence: 99%